Evaluation of Simpler Criteria for Diagnosing Allergic Bronchopulmonary Aspergillosis Complicating Asthma - Ritesh Agarwal; Puneet Saxena; Valliappan Muthu; Inderpaul Singh Sehgal; Sahajal Dhooria; Kuruswamy Thurai Prasad; Ashutosh Nath Aggarwal; Arunaloke Chakrabarti (Frontiers in Cellular and Infection Microbiology, 2022)
BackgroundThe modified International Society for Human and Animal Mycology (ISHAM) allergic bronchopulmonary aspergillosis (ABPA) working group (AWG) criteria lists up to five components for diagnosing ABPA in asthmatics. Whether eliminating specific components of the existing criteria would have the same diagnostic utility as the original remains unknown.ObjectiveTo evaluate the performance of several simplified criteria for diagnosing ABPA.MethodsWe compared the performance of seven new criteria (after excluding or modifying one or more of the components of the ISHAM-AWG criteria) with the modified ISHAM-AWG criteria in asthmatic subjects using latent class analysis (LCA). We also tested the performance of the newer criteria using accuracy measures against a multidisciplinary team (MDT) diagnosis of ABPA. We considered the diagnostic accuracy of the newer criteria to be acceptable if the correct classification and false-negative rates were >95% and <5%, respectively, on an MDT evaluation.ResultsWe analyzed data from 543 asthmatic subjects (58.8% women; mean age, 36.8 years). Using LCA, the sensitivity of the A.fumigatus-specific IgE-based criteria ranged from 92-99%, while the specificity varied between 92% and 100%. The MDT diagnosed ABPA in 106 (19.5%) subjects. Using MDT as the reference standard, the correct classification and false-negative rates were >95% for three of the seven and <5% for four of the seven newer criteria.ConclusionsWe found several of the newly developed criteria to perform, like the modified ISHAM-AWG criteria, for diagnosing ABPA complicating asthma. A prospective study in current clinical algorithms is required for validating our observations.